Konseling Rational Emotive Behavior Untuk Menurunkan Perilaku Mencontek Siswi - Holil, Zainul Holil; Majdi, M. Zuhdi Zainul Majdi (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi Pancor, 2025)
In discipline of education, there is a problem where cheating is perceived as a type of violation of educational discipline; if it is tolerated, then indirectly education operates in a fake state so that it does not produce the best outcomes. This study was to determine the effectiveness of counseling applying rational emotive behavior in reducing female students' cheating behavior. This study used a one-group pretest-posttest design. Seven people were the study's subjects. Purposive sampling is the method of sample elimination used. An assessment of cheating behavior was used to collect data. Data analysis using statistical t-test. The research results indicated that the rational emotive behavior technique had a positive impact on reducing female students' cheating behavior Keywords : Counseling Rational Emotive Behavior, Cheating Behavior